Genetic Diversity of Global Faba Bean Germplasm Resources Based on the 130K TNGS Genotyping Platform - Hongyan Zhang; Yujiao Liu; Xuxiao Zong; Changcai Teng; Wanwei Hou; Ping Li; Dezhi Du (Agronomy, 2023)
Novel germplasm resources are the key to crop breeding, with their genetic diversity and population structure analysis being highly significant for future faba bean breeding. We genotyped 410 global faba bean accessions using the 130K targeted next-generation sequencing (TNGS) genotyping platform, resulting in a total of 38,111 high-quality SNP loci by high-standard filtering. We found the polymorphism information content (PIC) and Nei’s gene diversity were 0.0905–0.3750 and 0.0950–0.5000, with averages of 0.2471 and 0.3035, respectively. After evaluating the genetic diversity of 410 accessions using Nei’s gene diversity and PIC, on the basis of their geographical origin (continent) and structure-analysis-inferred subpopulations, we found that the faba bean accessions from Asia (except China) and Europe had rich genetic diversity, while those from the winter sowing area of China were low. The 410 faba bean accessions were divided into four subpopulations according to population structure analysis and clustering analysis based on Nei’s (1972) genetic distance using the neighbor-joining (NJ) method. However, the same subpopulation contained materials from different geographical origins, thereby indicating that the gene flow or introgression occurred among the accessions. Results from NJ clustering based on shared allele genetic distance indicated that the 410 accessions were divided into three groups according to their dissemination routes. The genetic diversity analysis results demonstrated that the genetic relationships among the faba bean groups with similar ecological environments and geographic origins in neighboring regions or countries were closer and frequently found within the same group, while genetic variation among individuals was the main source of their total genetic variation.